Proceedings of the Workshop Contemporary Geometry and Related Topics : (World Scientific, 2002)
Book is collection of document in Proceedings of the Workshop Contemporary Geometry and Related Topics was held in Belgrade, Yugoslavia, 15-21 May 2002